Physically modified of sweet potato flour (Ipomea batatas) by variation of steaming time and drying method - Anshar Patria; Nida El Husna; Yanti Meldasari Lubis; Melly Novita (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The major component of sweet potato flour is carbohydrate presented as starch. As other types of native starch that lack of physical and chemical characteristics, the sweet potato flour then is very limited in use. To improve the starch characteristics, it can be made by modifying the starch physically. This study was focused on modification of starch phisically by using autoclaving-cooling method with differ in steaming times (15 and 30 minutes) and drying methods (oven and sun drying). The results showed that the modified flour of sweet potato by autoclaving-cooling for one cycle has produce sweet potato flour with a granular structure that can expand and break, lower in starch content, higher in freezing and thawing stability, higher in water absorption index, and lower in hot and cooling viscosities